Philippe Vandermaelen, Mercator de la jeune Belgique - Marguerite Silvestre (Brussels Studies, 2016)
This article presents the conclusions of a book published concomitantly by the Bibliothèque royale de Belgique: Philippe Vandermaelen, Mercator de la jeune Belgique. Histoire de l’Établissement géographique de Bruxelles et de son fondateur. This publication is the result of twenty-five years of research in the Maps & Plans section, the depository of the exceptional cartographic and documentary collection from the Établissement géographique de Bruxelles. The article and work it refers to present the life of the visionary geographer in a chronological journey centred on his cartographic production (methodology, collaborations, surveys, levelling, commercial management, etc.), ending with a passing of the baton to the Dépôt de la Guerre, the future Institut géographique national. It also opens the doors to Vandermaelen’s different institutional creations in a cross-cutting approach: the documentation centre, the natural history gallery, the lithography school and the École Normale, the museum of ethnography, and the organisation of scientific expeditions.